2020
DOI: 10.1021/acsmacrolett.0c00170
|View full text |Cite
|
Sign up to set email alerts
|

Azobenzene-Based Ionic Liquid Switches Phase Separation of Poly(N-isopropylacrylamide) Aqueous Solutions as a Molecular Trigger, Leading to UV Shutdown of Ionic Transport

Abstract: This paper presents a light-switchable phase separation of poly­(N-isopropylacrylamide) (PNIPAm) in aqueous solutions using an azobenzene-based ionic liquid as a molecular trigger. A different UV response was obtained with use of an azobenzene molecular trigger. A UV-induced aggregation of PNIPAm was observed in the current system, which is opposite to that reported for azobenzene-functionalized PNIPAm systems. According to in situ FT-IR, cis-isomers destabilized the hydrogen bonding between water and PNIPAm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Temperature‐dependent 1 HNMR also suggested that azobenzene‐based ILs stayed in PNIPAm aggregated phase rather than in water phase. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature‐dependent 1 HNMR also suggested that azobenzene‐based ILs stayed in PNIPAm aggregated phase rather than in water phase. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 16,17 ] Very recently, we reported another method that an azobenzene‐based ionic liquid(IL) located in a “solvent,” rather than in a “solute” (azobenzene‐functionalized polymers), could tune LCST behaviors of PNIPAm in water. [ 18 ] It showed light controlled LCST phase transitions of PNIPAm in water at ambient temperatures. This method could avoid polymerization of azobenzene components since azobenzene monomers were not always conducive to the polymerization process and azobenzene in a molecular position was in favor of rapid phase separation behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Till now, the reported works mainly concentrated on the polarity modulation of photoisomerizable moieties via illumination to control the ionic conductivity. Generally, it will take some time for photoisomerizable moiety-containing polymers to reach the photostationary state upon illumination 19 , 20 , 23 . The response time is substantially decided by the polymer selection and composite structures.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it will take some time for photoisomerizable moiety-containing polymers to reach the photostationary state upon illumination. 19,20,23 The response time is substantially decided by the polymer selection and composite structures. Therefore, an elaborate polymer composite of UV responsive polymers effectively integrated with ILs is highly desired for sensitive UV detectors.…”
Section: Introductionmentioning
confidence: 99%